160k views
3 votes
Evaluate the expression for x = 2. -9x2 + 11x − 7 =

User CyberRobot
by
5.3k points

2 Answers

2 votes

Follow order of operations.

(Replace x with 2)

-9x2 + 11x − 7 =

-9(2)*2+11(2)-7

-9*2=-18*2= -36

11*2=22-7= 15

-36+15 = -21

Answer: -21 :)

- Liebesleid


User Shamima
by
6.6k points
3 votes

All you have to do is replace every x with 2 and then solve:

Make to sure to follow the Order of Operations!!

-9x(2) + 11x - 7 =

(-9 × 2 × 2) + (11 × 2) - 7 =

-36 + 22 - 7 =

-14 - 7 =

-21

The answer is -21.

Hope that helps!


User Choco
by
6.9k points